2018
DOI: 10.1021/acssuschemeng.8b01701
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Hydrogen Production by Direct Electrolysis of Waste Biomass at Intermediate Temperatures

Abstract: Biomass has been considered as an alternative feedstock for energy and material supply. However, the lack of high-efficiency and low-cost processes for biomass utilization and conversion hinders its large-scale application. This report describes electrochemical hydrogen production from waste biomass that does not require large amounts of energy or high production costs. Hydrogen was produced by the electrolysis of bread residue, cypress sawdust, and rice chaff at an onset cell voltage of ca. 0.3 V, with high c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(34 citation statements)
references
References 36 publications
1
33
0
Order By: Relevance
“…Hydrogen, apromising renewable energy resource, can be produced by variousm ethods such as steam reforming of natural gas, thermolysis, electrolysis, photobiological water splitting and photocatalytic water splitting. [1][2][3][4] Among these methods, photocatalytic water splitting is considered as an environmentally friendly,e fficient, simple and cost-effective process because it utilizes earth-abundant water and solarl ight to produce hydrogen in the presenceo fareusable photocatalyst. However,f or the commercial viability of the photocatalytic hydrogen production method, the solar to hydrogenc onversion (STH) efficiency should be at least 10 %.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen, apromising renewable energy resource, can be produced by variousm ethods such as steam reforming of natural gas, thermolysis, electrolysis, photobiological water splitting and photocatalytic water splitting. [1][2][3][4] Among these methods, photocatalytic water splitting is considered as an environmentally friendly,e fficient, simple and cost-effective process because it utilizes earth-abundant water and solarl ight to produce hydrogen in the presenceo fareusable photocatalyst. However,f or the commercial viability of the photocatalytic hydrogen production method, the solar to hydrogenc onversion (STH) efficiency should be at least 10 %.…”
Section: Introductionmentioning
confidence: 99%
“…The partially oxygenated carbon anode used in this study was synthesized according to a procedure reported previously [15,16]. Briefly, 1.0 g of Ketjen Black (KB) was stirred in 24% HNO 3 diluted to 50 mL at room temperature for 74 h. After filtering and washing, the oxygenated KB was heated at 600 • C for 4 h under an Ar flow to eliminate carboxyl groups preferentially (as opposed to carbonyl groups having higher thermal stability) from the carbon surface.…”
Section: Resultsmentioning
confidence: 99%
“…Electrolysis at elevated temperatures is also advantageous for the kinetic characteristics of the used electrodes. A recent report indicated a lignocellulosic biomass electrolysis cell using partially oxygenated carbon as the anode at temperatures above 125 • C [15,16]. However, Pt was still necessary for the hydrogen evolution reaction (HER) at the cathode in this cell.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the available heating source (e.g., nuclear station) is limited. Therefore, intermediate temperature SOEC (IT‐SOEC) that operates around 500–700 °C has recently attracted great interests . Doped ceria is one of the most promising electrolyte materials for IT‐SOEC because of its high oxygen ion conductivity (10 −2 S cm −1 at 600 °C) at intermediate temperature .…”
mentioning
confidence: 99%
“…Therefore, intermediate temperature SOEC (IT-SOEC) that operates around 500-700 C has recently attracted great interests. [6,7] Doped ceria is one of the most promising electrolyte materials for IT-SOEC because of its high oxygen ion conductivity (10 À2 S cm À1 at 600 C [8] ) at intermediate temperature. [9] The main problem of doped ceria electrolyte is its strong tendency to reduce Ce 4þ to Ce 3þ during operation.…”
mentioning
confidence: 99%